2017
DOI: 10.1063/1.4990082
|View full text |Cite
|
Sign up to set email alerts
|

From two-dimensional to three-dimensional turbulence through two-dimensional three-component flows

Abstract: The relevance of two-dimensional three-components (2D3C) flows goes well beyond their occurrence in nature, and a deeper understanding of their dynamics might be also helpful in order to shed further light on the dynamics of pure two-dimenional (2D) or three-dimensional (3D) flows and vice versa. The purpose of the present paper is to make a step in this direction through a combination of numerical and analytical work. The analytical part is mainly concerned with the behavior of 2D3C flows in isolation and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
8
28
0
Order By: Relevance
“…So while the total flux is zero, this is achieved by the dynamical balance of the channels that bring energy forwards (the heterochiral) and the ones that bring it backwards (the homochiral). The same phenomenon has been observed in flows composed by a combination of 2D3C (two dimension, three component) flows [44]. The amplitude and range of modes that are involved in this flux balance does depend slightly on the rotation rate, with simulation PRJ-A3 being the one with the largest number of modes that had non-zero flux in the homo and heterochiral channels.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…So while the total flux is zero, this is achieved by the dynamical balance of the channels that bring energy forwards (the heterochiral) and the ones that bring it backwards (the homochiral). The same phenomenon has been observed in flows composed by a combination of 2D3C (two dimension, three component) flows [44]. The amplitude and range of modes that are involved in this flux balance does depend slightly on the rotation rate, with simulation PRJ-A3 being the one with the largest number of modes that had non-zero flux in the homo and heterochiral channels.…”
Section: Resultssupporting
confidence: 68%
“…If resonant interactions can make the energy transfer anisotropic, aren't they also contributing to the inverse transfer of energy? Moreover, it has been shown that even in fully homogeneous and isotropic three dimensional turbulence, there are channels that take energy backwards [14,15], that the action of these channels can be enhanced in different geometries [44], and that these channels can couple the 2D and 3D modes in rotating turbulence [36]. This adds a further avenue to explore.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that no additional friction is required to prevent the energy from accumulating at large scales may also be explained by alternative mechanisms. Scenarios according to which simultaneous upward and downward cascades coexist were in particular recently evidenced in 2D3C flows [28] but do not need to be invoked here to explain the damping because of the presence of walls. Figure 2(b) shows typical instantaneous flow fields in the stationary state.…”
Section: B Steady Helical Flowsmentioning
confidence: 98%
“…As mentioned above, Π HO + (k) and Π HO − (k) contribute to a subleading inverse energy transfer even in 3D. Their combined contribution is the total homochiral flux [18,36] Π HO (k) = Π HO…”
Section: Fluxes and Nonuniversal Dynamicsmentioning
confidence: 92%